Comparison of aerobic and anaerobic performances of well trained wrestlers according to weights - Ari, Y.; Tuncel, A. (Kinesiologia Slovenica, 2021)
The aim of this study is to examine the aerobic and anaerobic performances of well trained wrestlers according to their weights. 19 young female wrestlers (age: 18.84 ± .83 years; height: 165.84 ± 4.58 cm; weight: 62.78 ± 8.81 kg; body mass index (BMI): 22.80 ± 2.94 kg/m2) voluntarily participated in this study. Body weight, height, BMI, sprint, agility, jump, flexibility and 20 m shuttle run tests of the wrestlers were measured. The data obtained were recorded according to the weights of the athletes. One Factor Analysis of Variance and Kruskal Wallis H test were used to analyze the data. Tukey`s multiple comparison test was conducted to find the difference between the groups. As a result of the study, a statistically significant difference was determined in terms of height, weight and BMI values of the wrestlers according to their weights (p<0.05). Significant differences were found between light and heavy weight groups in view of speed, agility, jumping, flexibility and shuttle running test performances (p<0.05). A statistically significant difference was found between the middle and heavyweight groups in speed and agility tests (p<0.05). This research shows that, the performance output of the athlete decreases as their weight increases.